Moyen de conversion ou encadrement du converti : usage du livre synodal à l’époque médiévale (XIIIe siècle) - Gaëtan Pierrard (Cahiers d'Études du Religieux- Recherches Interdisciplinaires)
The use of the synodal book in the practice of the Christian religion must be perceived as a protective rampart of the converted popular masses. Once converted, these last ones henceforth have to submit themselves in a set of rules set up to manage and control these new units which constitute the base and the reason for being of this faith, to which they adhered. The action of the synod so allows the institution to base its authority on the convert by imposing him a certain number of criteria to be filled. In this context, the XIIIth century plays a pivotal role.